2010
DOI: 10.1016/j.juro.2009.12.102
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Open or Robotic Prostatectomy, Cryoablation or Brachytherapy for Localized Prostate Cancer

Abstract: In a study of sequential health related quality of life assessments brachytherapy and cryotherapy were associated with higher urinary function and bother scores compared to open radical prostatectomy and da Vinci prostatectomy. Brachytherapy was associated with higher sexual function and bother scores compared to open radical prostatectomy, robotic assisted laparoscopic radical prostatectomy and cryotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 23 publications
5
81
1
4
Order By: Relevance
“…91,95,96 Of the non-randomised comparative studies comparing robotic, laparoscopic and open radical prostatectomy, two primary studies 99,100 and one secondary report 102 were set in the USA and one study was set in France. 101 Of the nonrandomised comparative studies comparing robotic and open radical prostatectomy, 10 primary studies 103,[108][109][110][111][112][115][116][117][118] and two secondary reports 119,120 were set in the USA, one study was set in Australia, 105 three primary studies 106,107,114 were set in Italy, one study was set in Sweden 104 and one was set in Taiwan, Province of China. 113 Of the non-randomised comparative studies comparing laparoscopic and open radical prostatectomy, seven primary studies [124][125][126]128,142,145,146 and one secondary report 147 were set in the USA, three primary studies 127,131,137 were set in Germany, three primary studies 135,136,144 were set in Japan, three primary studies 123,129,134 were set in Italy, two primary studies 122,140 were set in France and one study each was set in Austria, 139 Brazil,…”
Section: Number and Type Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…91,95,96 Of the non-randomised comparative studies comparing robotic, laparoscopic and open radical prostatectomy, two primary studies 99,100 and one secondary report 102 were set in the USA and one study was set in France. 101 Of the nonrandomised comparative studies comparing robotic and open radical prostatectomy, 10 primary studies 103,[108][109][110][111][112][115][116][117][118] and two secondary reports 119,120 were set in the USA, one study was set in Australia, 105 three primary studies 106,107,114 were set in Italy, one study was set in Sweden 104 and one was set in Taiwan, Province of China. 113 Of the non-randomised comparative studies comparing laparoscopic and open radical prostatectomy, seven primary studies [124][125][126]128,142,145,146 and one secondary report 147 were set in the USA, three primary studies 127,131,137 were set in Germany, three primary studies 135,136,144 were set in Japan, three primary studies 123,129,134 were set in Italy, two primary studies 122,140 were set in France and one study each was set in Austria, 139 Brazil,…”
Section: Number and Type Of Included Studiesmentioning
confidence: 99%
“…Less than half of the included reports (23/58, 40%) 91,98,99,101,103,[105][106][107][108]110,115,[117][118][119][120][121]125,128,135,136,142,145,146 gave detailed biopsy Gleason scores for men undergoing prostatectomy in the format we required: numbers of men categorised as Gleason score ≤ 6, 7 or ≥ 8. Seven studies 90,95,97,111,126,139,141 and one secondary report 147 did not report biopsy Gleason grades or score.…”
Section: Characteristics Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…da her iki yöntemin yaşam kalitesi açısından benzer sonuçlara sahip olduğunu belirtmişlerdir. Lokalize prostat kanseri nedenli ARP, RRP, brakiterapi, kriyoablasyon yapılan hastaların karşılaştırıldığı geniş hasta sayılı bir diğer çalışmada ise brakiterapi ve kriyoablasyon tedavilerin cerrahi yöntemlere göre daha az seksüel ve üriner sorun oluşturduğu ve bu tedavilerde yaşam kalitesinin daha iyi olduğu sonucu bulunmuştur (21). Ancak bu tür lokal ablatif tedavilerin yan etkilerinin uzun dönemde ortaya çıktığı bilindiğinden bu sonuçlar da sorgulanabilir niteliktedir.…”
Section: Yaşam Kalitesi Açısından Robotik Radikal Prostatektomiunclassified
“…Generally, men treated with cryotherapy report higher prevalence of urinary symptoms compared with RP in the short term, but the symptoms improve or disappear after ≥ 3 months 68, 69. A 2‐year follow‐up observational study of 10,928 men comparing BT vs. cryotherapy demonstrated that cryotherapy was associated with more urinary complications than BT 70.…”
Section: Introductionmentioning
confidence: 99%